Early Diagnosis of Mild Cognitive Impairment Based on Eye Movement Parameters in an Aging Chinese Population - Nie, Jing; Qiu, Qi; Phillips, Michael; Sun, Lin; Yan, Feng; Lin, Xiang; Xiao, Shifu; Li, Xia (Frontiers in Aging Neuroscience, 2020)
Background: The pathogenesis of dementia often starts several years prior to clinical onset during which the individual is asymptomatic. Eye movement parameters associated with cognitive functions may be helpful in the early identification of dementia and in the development and evaluation of preventive and therapeutic strategies. Objective: We aimed to assess differences in eye movement parameters between healthy controls and MCI population. Furthermore, we examined the correlations between novelty preference(NP) score with cognitive functions and specific hemispheric region and neural structures in individuals with MCI. Method: 80 individuals with MCI identified by community screening and 170 healthy controls were administered Chinese versions of MoCA and NTB, and a long (20 minutes) or short (5 minutes) version of a visual paired comparison (VPC) task. Two weeks later 44 MCI patients and 107 healthy controls completed a re-test of the VPC task, 44 MCI patients and 43 healthy controls among them administered a MRI. At the end of one year follow-up, 26 MCI patients and 57 healthy controls were administered the long version of VPC task and MoCA test again. The NP score, and the relationship with cognitive functions and with changes in neural structures were compared between groups. Results: Patients with MCI were older, had less education, and had lower scores on cognitive tests than healthy controls. Patients with MCI had lower NP scores on the VPC than healthy controls. Using the logistic regression model, NP scores could predict MCI patients from normal elderly.Furthermore, the cognition score of subjects whose NP score was low decreased more remarkably in one year. For both MCI and control groups NP score was significantly correlated with verbal fluency, delayed and short-term memory function. NP score was also significantly correlated with the cortical thickness of several structures in the right hemisphere Conclusion: Eye movement parameters are stable indicators to distinguish patients with MCI and cognitively normal subjects and are not affected by different testing versions and numbers. Additionally, the patients’ cognitive deficits and eye movement indices were correlated. Future longitudinal studies should further explore the clinical utility of eye movement parameters as early markers of MCI.